Symbol Elimination for Automated Generation of Program Properties - Kovacs, Laura (Electronic Communications of the EASST, 2014)
Automatic understanding of the intended meaning of computer programs is a very hard problem, requiring intelligence and reasoning. In this talk we describe applications of our symbol elimination methods in automated proram analysis. Symbol elimination uses first-order theorem proving techniques in conjunction with symbolic computation methods, and derives nontrivial program properties, such as loop invariants and loop bounds, in a fully automatic way. Moreover, symbol elimination can be used as an alternative to interpolation for software verification.